Roxadustat for Anemia in Patients with Kidney Disease Not Receiving Dialysis - Chen, Nan; Hao, Chuanming; Peng, Xiaomei; Lin, Hongli; Yin, Aiping; Hao, Li; Tao, Ye; Liang, Xinling; Liu, Zhengrong; Xing, Changying; Chen, Jianghua; Luo, Laimin; et al. (The New England journal of medicine, 2019)
This phase 3, randomized trial in China compared the efficacy and safety of roxadustat, an oral hypoxia-inducible factor prolyl hydroxylase inhibitor, with placebo for anemia in patients with CKD who were not undergoing dialysis. Roxadustat was superior to placebo in increasing and maintaining hemoglobin levels.